Zeolite A, X and Cancrinite from South African coal fly ash: mechanism of crystallization, routes to rapid synthesis and new morphology - Musyoka, Nicholas Mulei (University of the Western Cape, 2015)
Philosophiae Doctor - PhD === In South Africa, almost 90 % of the country’s electricity is generated from coal combustion. This reliance on coal for energy production is projected to continue in the near and medium term due to the increasing demand for industrial and domestic energy. During coal combustion, a large quantity of fly ash is produced as the main waste product and in South Africa approximately 36 - 37 million tons of fly ash is produced on a yearly basis. The management of huge quantities of fly ash has been and still is a continuing challenge that requires urgent intervention. In this regard, there exists an urgent need to maximize fly ash beneficiation, thus forming the motivation for this research. The overall objectives of this thesis was to synthesize high pure phase zeolites A and X from South African fly ash, study their formation mechanism, and explore the potential of mine waters during the synthesis process as well as developing new and efficient zeolite synthetic protocols by the use of ultrasound. In order to address these objectives, the research was designed in a sequential manner so that the preceding results could act as a platform for the attainment of the next objective. In this case, the identification and optimization of synthesis conditions for producing zeolite A and X acted as a basis for understanding the influence of use of mine waters as a substitute for pure water. This further laid the foundation for the in-situ ultrasonic monitoring of the formation process of zeolite A and X from fly ash. The final stages of the study involved use of ultrasonic energy as an ageing tool to improve the conditions obtained during the hydrothermal synthesis of zeolite A as well as investigate the potential to synthesize zeolites directly by use of ultrasound without the need for the fusion, aging or conventional hydrothermal treatment step. The result of the optimized synthesis conditions for producing zeolite A starting either from clear extract of fused fly ash or unseparated, fused South African class F fly ash slurry were molar regimes of 1 Al2O3 : 30.84 Na2O : 4 SiO2 : 414.42 H2O or 1 Al2O3 : 5.39 Na2O : 2.75 SiO2 : 111.82 H2O respectively and at a hydrothermal synthesis temperature of 100 °C for 2 hours. The optimized procedure was simple, efficient and resulted in a considerable improvement of the quality and phase purity of the zeolite A product when the clear extract of fused fly ash was used instead of starting from unseparated, fused fly ash slurry. On the other hand, the optimized synthesis conditions for preparing the typical octahedral shaped zeolite X from South African fly ash was found to be a molar regime of 1 Al2O3 : 4.90 Na2O : 3.63 SiO2 : 115.92 H2O at a hydrothermal synthesis temperature of 80 ºC for hours.